1965
DOI: 10.1071/bi9650053
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Sugar-Cane VII. Effects of Temperature, Photoperiod Duration, and Diurnal and Seasonal Temperature Changes on Growth and Ripening

Abstract: Independent and interaction effects of day and night temperature, photo-period duration, and diurnal thermoperiodicity were studied on sugar-cane grown under controlled environments. During the first 3 months of growth, day and night temperature effects were mainly additive, but at 6 months the interaction effects of all variables were numerous and complex. Many of the interaction effects could be attributed to increased responses to constant-temperature regimes with a 12-hr photoperiod. No evidence for thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
10

Year Published

1972
1972
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 2 publications
1
10
0
10
Order By: Relevance
“…Both Dale (1964) and Hussey (1965) investigated the validity of the concept of thermoperiodism in young plants of French bean and tomato, but could find little evidence of this phenomenon. Glasziou et al (1965) and Robson (1973) have also studied the effect of diurnal temperature variation on growth in sugar cane and tall fescue and have similarly concluded that there was no evidence of thermoperiodism in these species, even though it is evident from their data that for the same mean daily temperatures a diurnal temperature variation gave higher growth rates than a constant temperature.…”
Section: ("C)mentioning
confidence: 91%
“…Both Dale (1964) and Hussey (1965) investigated the validity of the concept of thermoperiodism in young plants of French bean and tomato, but could find little evidence of this phenomenon. Glasziou et al (1965) and Robson (1973) have also studied the effect of diurnal temperature variation on growth in sugar cane and tall fescue and have similarly concluded that there was no evidence of thermoperiodism in these species, even though it is evident from their data that for the same mean daily temperatures a diurnal temperature variation gave higher growth rates than a constant temperature.…”
Section: ("C)mentioning
confidence: 91%
“…It is clear that sucrose production is highest when fully canopied crops are intercepting high levels of solar radiation (Glasziou et al 1964, cited in Yates 1986. This is true when temperature variations through the year are low, which is the case in crops grown close to the equator (Yates 1986).…”
Section: Temperaturementioning
confidence: 99%
“…Respiration rates are reduced more by low temperatures than are rates of photosynthesis (Glasziou et al 1964, cited in Yates 1986Glover 1973) and, by implication, a greater portion of photosynthate is available for storage when temperatures are low (Glover 1973). Waldron et al (1967) showed that photosynthetic efficiency fell at low temperatures (17 • C), and culm growth declined but sucrose content continued to increase.…”
Section: Temperaturementioning
confidence: 99%
See 2 more Smart Citations